Heat of Mixing of some Binary Liquid Alloys - Kanth, BK; Chakrabarti, SK (Scientific World, 2010)
There are a large number of binary liquid alloys the thermodynamic properties of mixing of which are not symmetrical about the equi-atomic composition-deviating maximally from those of the ideal alloys. Here we have considered three such alloys-indium-sodium, cadmium-sodium and copper-tin-and tried to calculate their heat of mixing at different concentrations of the ingredients. The liquidus lines of these alloys reveal that the constituent species form complexes. So, we have considered a quasi-lattice chemical model for computation of the thermodynamic entities. It is a statistical model in which grand partition function is used assuming that the energy of a given nearest neighbour bond is different if it belongs to the complex than if it does not. For each alloy we have started with the expression for excess free energy of mixing according to this model and computed the free energy of mixing for different concentrations of the metals within it by deriving the value of interaction parameters through successive approximation method. Thereafter, the expression for excess entropy of mixing is taken into account and the entropy of mixing is computed for different concentrations after finding out the temperature derivative of interaction parameters by the method of successive approximation. Finally the heat of mixing is calculated from these free energy of mixing and entropy of mixing on using the standard thermodynamic relation. The results explain the observed asymmetry in the heat of mixing of the said binary liquid alloys around equi-atomic composition. Key words : Binary liquid alloy; Quasi-lattice chemical model; Heat of mixing DOI: 10.3126/sw.v7i7.3836 Scientific World Vol.7(7) 2009 pp.96-99